Sources of short-term financing, their costs, challenges and effectiveness: the perspective of a Bangladeshi construction company - Western Engineering (Pvt.) Ltd. - Hossain, Md. Ismail (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.